Differences in Student Engagement: Investigating the Role of the Dominant Cognitive Processes Preferred by Engineering and Education Students. (11th November 2010) - Ball, Ian; Perry, Chris
Abstract : This paper reports on a study of the differences in the dominant cognitive processes preferred by groups of engineering and education students and examines the implications of these differences for the assessment of student engagement with university courses. Concern is expressed that the items commonly used to capture student engagement data do not adequately cover the full range of the dominant cognitive processes preferred by tertiary students. The paper sets out a brief overview of student engagement along with the theory of dominant and auxiliary cognitive processes, as developed by Jung and later by Myers. Evidence is presented of the differing frequencies of the eight cognitive processes, as assessed by the Myers-Briggs Type Indicator, that are preferred by cohorts of students undertaking courses in engineering and education. The implications of these differences are discussed in the context of subject disciplines in university environments.